Di-Iron Trioxide Hydrate-Multi-Walled Carbon Nanotube Nanocomposite for Arsenite Detection Using Surface Plasmon Resonance Technique - Kamil, Yasmin Mustapha; Al-Rekabi, Sura Hmoud; Mohamed, Husam Abduldaem; Bakar, Muhammad Hafiz Abu; Kanagesan, Samikannu; Fen, Yap Wing; Mahdi, Mohd Adzir (Institute of Electrical and Electronics Engineers (IEEE), 2019)
We present surface plasmon resonance-based sensor for arsenite [As(III)] detection using Di-iron trioxide hydrate - multi-walled carbon nanotube (Fe2H2O4-MWCNT) nanocomposite as a sensing layer. The enticing traits of Fe2H2O4-MWCNT having high surface to volume ratio and good affinity toward arsenic have proven to enhance As(III) absorption onto the sensing surface and consequently increase the sensitivity of the sensor. When tested with different concentrations of As(III) within the range of 0.2 ppb to 1 ppb, sensitivity value was obtained at 1.756° ppb−1 with Fe2H2O4-MWCNT thickness of 7 nm. The detection limit was achieved at 0.2 ppb which surpassed conventional methods and reported studies on SPR-based sensor for As detection. © 2020 Copyright held by the owner/author(s). Publication rights licensed to ACM.